MULLER, Pierre. Les politiques publiques. Presses Universitaires de France, Paris, 9ª. Edição, 2011. - Silva, Isabelle Fiorelli (Jornal de Políticas Educacionais, 2012)
Resenha da obra do autor francês Pierre Muller